DIAGNOSING CARDIOMEGALY USING POSTMORTEM COMPUTED TOMOGRAPHY (PMCT) IN SUDDEN DEATH POSTMORTEM CASES (Journal of Forensic Medicine & Toxicology, 2017)
Cardiothoracic ratio (CTR) is a simple method used to measure or indicate any abnormality of the heart. It is an aid in detection of cardiomegaly, or more broadly the enlargement of cardiac silhouette. This study is to compare the 3 methods based on the PMCT radiological reading versus the gold standard method using heart weight and 0.5% body weight ±0.05kg (Method D) in sudden death cases at HKL. All the sudden natural death cases that have been scanned using PMCT within Apr-Dec 2015 were included with total sample size of 126. There were 113 males and 13 females within range from 19 to 78 years old based on the convenience sampling. Exclusion criterias are the dead bodies with unknown identity and age below 18 years-old. In this retrospective study, the maximal transverse cardiac diameter “T”, maximal transverse thoracic diameter “C”, both diagonal diameters with long axis “L” and short axis “S” were measured. Three radiological methods were namely Method A: Transverse CTR = T/C; Method B: CTR index = (L+S)/2)/C; and Method C: CTR index = (T+S)/2)/C. Cardiomegaly indicated if CTR or index e”0.5 ±0.05. There was no significance difference with pe”0.05 using Paired-T Test and the decision values did not deviated further among these 4 methods. Only Method B and Method C were both correlate strongly between each other with p
Keywords: Cardiomegaly; Postmortem Computed Tomography (PMCT); Sudden Death; Heart Measurement